2015
DOI: 10.1002/mas.21476
|View full text |Cite
|
Sign up to set email alerts
|

Charged supramolecular assemblies of surfactant molecules in gas phase

Abstract: The aim of this review is to critically analyze recent literature on charged supramolecular assemblies formed by surfactant molecules in gas phase. Apart our specific interest on this research area, the stimuli to undertake the task arise from the widespread theoretical and applicative benefits emerging from a comprehensive view of this topic. In fact, the study of the formation, stability, and physicochemical peculiarities of non-covalent assemblies of surfactant molecules in gas phase allows to unveil intere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 86 publications
0
13
0
Order By: Relevance
“…Mild ionization techniques as Fast‐Atom Bombardment (FAB), Matrix‐Assisted Laser Desorption/Ionization (MALDI) and mainly Electrospray Ionization (ESI) were preferred in our and several other studies …”
mentioning
confidence: 91%
See 1 more Smart Citation
“…Mild ionization techniques as Fast‐Atom Bombardment (FAB), Matrix‐Assisted Laser Desorption/Ionization (MALDI) and mainly Electrospray Ionization (ESI) were preferred in our and several other studies …”
mentioning
confidence: 91%
“…[5,6] Mild ionization techniques as Fast-Atom Bombardment (FAB), Matrix-Assisted Laser Desorption/Ionization (MALDI) and mainly Electrospray Ionization (ESI) were preferred in our and several other studies. [7][8][9][10] The study of surfactant self-assembly in the gas phase as charged aggregates constitutes a developing research field of interest since it allows information to be gained on their structural organization in the absence of surrounding interactions with the solvents as well as to exploit their use as gas-phase cleaning agents, vehicles of pulmonary drugs, specialized reactors for the synthesis of nanostructures and particularly for the chemical protection of biomolecules in mass spectrometric studies. [11,12] The majority of studies concerning the structural organization of these charged aggregates in the gas phase suggest that surfactant molecules are organized as reverse micelle-like assemblies, independently of the aggregate charge state and ESI solvent used.…”
mentioning
confidence: 99%
“…reported that the structural organization of the surfactant in the gas phase depended on the nature and composition of the starting solution . The structure formed in the gas phase and detected by mass spectrometry results from a concurrence of the relative rates of evaporation of the dilution solvent, spontaneous transfer of surfactant molecules at the droplet surface, and aggregate structural rearrangements . In nonpolar media, such as alkanes, TBP is organized in small reverse aggregates,,,, whereas in methanol/water media it is likely that only molecular complexes are present in solution.…”
Section: Resultsmentioning
confidence: 99%
“…Also MD calculations are consistent with the occurrence of OH‐‐‐Br hydrogen bonding in large positively and negatively charged aggregates. On the other hand, the MD models that give CCS values in good agreement with experimental ones evidenced a less strict reverse micelle‐like structure and a more spread bromine anion distribution with respect to other supramolecular surfactant aggregates reported elsewhere …”
Section: Discussionmentioning
confidence: 99%
“…The study of charged aggregates of surfactant molecules in the gas phase is of growing interest both for theoretical and technological reasons . The main fallout of these investigations is the knowledge of the structural organization of the aggregates and of the mechanism through which amphiphilic molecules self‐assemble during the strongly out of equilibrium conditions characterizing the electrospray ionization process.…”
mentioning
confidence: 99%